2022
DOI: 10.3390/jpm12020280
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in Lipid and Glucose Levels Associated with Drug Use and Mortality: An Observational Study

Abstract: Background: The pathogenesis of type 2 diabetes mellitus is complex and still unclear in some details. The main feature of diabetes mellitus is high serum glucose, and the question arises of whether there are other statistically observable dysregulations in laboratory measurements before the state of hyperglycemia becomes severe. In the present study, we aim to examine glucose and lipid profiles in the context of age, sex, medication use, and mortality. Methods: We conducted an observational study by analyzing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 70 publications
2
4
0
Order By: Relevance
“…These results align with previous research indicating that the prevalence of diabetes and its complications increases with age (56). Moreover, we found that the population of female individuals with diabetes reached its peak of prescribed medications a decade later than male individuals with diabetes, which is consistent with our previous findings on age-related changes in lipid and glucose levels associated with drug use and mortality (57). This observation underscores the importance of effective diabetes management, as diabetes-related mortality remains a significant public health (58, 59).…”
Section: Discussionsupporting
confidence: 93%
“…These results align with previous research indicating that the prevalence of diabetes and its complications increases with age (56). Moreover, we found that the population of female individuals with diabetes reached its peak of prescribed medications a decade later than male individuals with diabetes, which is consistent with our previous findings on age-related changes in lipid and glucose levels associated with drug use and mortality (57). This observation underscores the importance of effective diabetes management, as diabetes-related mortality remains a significant public health (58, 59).…”
Section: Discussionsupporting
confidence: 93%
“…The elevated FFAs also block the glucose entry [ 47 ], and in a vicious cycle with glucolipotoxicity, beta cells cannot efficiently sense glucose [ 86 , 87 ]. This is one of the most prominent pathways to the pathologies of metabolic syndrome and T2DM associated with obesity and hyperlipidemia, which are statistically observable [ 6 ] and represent an even greater problem in modern societies.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of lipids on glucose metabolism, particularly the role of ectopic lipid accumulation, requires a systemic approach in a complex circuit of the endocrine pancreas and its hormone-targeted tissues, especially the liver and muscle [ 3 , 4 ]. We and others have shown that hyperlipidemia may statistically precede hyperglycemia by several years [ 5 , 6 ], indicating that it is predictive of reduced glucose tolerance in certain individuals. In addition, insulin resistance and prediabetes, conditions closely associated with metabolic syndrome, are thought to be caused by disturbances in energy utilization and storage, which certainly include impaired lipid utilization.…”
Section: Introductionmentioning
confidence: 99%
“…They can establish risk models by learning from existing medical test or survey data of patients. These models are used for disease prediction ( 12 , 13 ), diagnosis of disease severity ( 14 ), and evaluation of disease prognosis ( 15 , 16 ). Our study explored the value of machine-learning methods for stroke prediction.…”
Section: Introductionmentioning
confidence: 99%